2004
DOI: 10.1038/sj.tpj.6500238
|View full text |Cite
|
Sign up to set email alerts
|

The functional mu opioid receptor (OPRM1) Asn40Asp variant predicts short-term response to nicotine replacement therapy in a clinical trial

Abstract: To determine whether the functional mu-opioid receptor (OPRM1) Asn40Asp variant predicts the comparative efficacy of different forms of NRT, we conducted a clinical trial of transdermal nicotine (TN) vs nicotine nasal spray (NS) in 320 smokers of European ancestry. Smokers carrying the OPRM1 Asp40 variant (n ¼ 82) were significantly more likely than those homozygous for the Asn40 variant (n ¼ 238) to be abstinent at the end of treatment, and reported less mood disturbance and weight gain. The genotype effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 61 publications
(58 reference statements)
6
131
2
Order By: Relevance
“…5 Our findings indicate that smokers homozygous for the DRD2 À141 Ins benefit more from bupropion treatment and persons with Ins/Del or Del/ Del genotypes at the DRD2À141 locus respond better to behavioral counseling or NRT. 5 Results from this study and others [6][7][8] may, in the future, help practitioners maximize the therapeutic benefit of pharmacological treatments for nicotine dependence.…”
Section: Introductionmentioning
confidence: 70%
“…5 Our findings indicate that smokers homozygous for the DRD2 À141 Ins benefit more from bupropion treatment and persons with Ins/Del or Del/ Del genotypes at the DRD2À141 locus respond better to behavioral counseling or NRT. 5 Results from this study and others [6][7][8] may, in the future, help practitioners maximize the therapeutic benefit of pharmacological treatments for nicotine dependence.…”
Section: Introductionmentioning
confidence: 70%
“…In a clinical trial where subjects were randomized to either transdermal nicotine patch or nasal spray, those with the Asp40 variant were more likely to be abstinent, and reported less weight gain and mood disturbances, compared to subjects homozygous for Asn40. 218 This effect was mainly observed in the nicotine patch group. 218 Bupropion is primarily metabolized to the active metabolite hydroxybupropion, and this is mostly mediated by CYP2B6 in vitro.…”
Section: Genetic Basis For Variations In Response To Smoking Cessatiomentioning
confidence: 93%
“…218 This effect was mainly observed in the nicotine patch group. 218 Bupropion is primarily metabolized to the active metabolite hydroxybupropion, and this is mostly mediated by CYP2B6 in vitro. 219,220 Lerman et al 221 examined the 1459C4T SNP (R487C), which decreases enzyme expression, 221,222 and reported subjects with at least one T allele were more likely to relapse and had higher cravings at EOT.…”
Section: Genetic Basis For Variations In Response To Smoking Cessatiomentioning
confidence: 93%
“…This is comparable to the reimbursement for smoking-cessation therapy for Medicare patients approved by the Centers for Medicare and Medicaid Services, which amounts to $197.92 for eight sessions per year (four sessions per attempt, up to two attempts annually). 60 A standard 8-week course of tapered TN therapy 23 costs $123.96 by the lowest available price listed on the www.drugstore.com online pharmacy web site. The current lowest available price for 10 weeks of bupropion (150 mg bid) is $127.50, and the current lowest available price for 12 weeks of varenicline (1 mg bid) is $314.95.…”
Section: Cost Of Smoking-cessation Treatmentmentioning
confidence: 99%
“…1,22 For example, smokers who carry the minor allele (Asp40) of the mu opioid receptor (OPRM1) Asn40Asp polymorphism have almost a twofold greater odds of abstinence with 8 weeks of NRT than those carrying the common Asn40 variant. 23 Similarly, smokers homozygous for the -141C Ins/Del Ins C allele in the dopamine receptor DRD2 gene have a 1.6-fold greater odds of abstinence with bupropion than those carrying at least one Del C allele, whereas smokers who have at least one copy of Del C have a 1.3-fold greater odds of abstinence on transdermal nicotine (TN) than Ins C homozygotes. 7 Other reports have suggested that genetic variation in nicotine-metabolizing enzymes (for example, CYP2A6 and CYP2B6) might also predict response to NRT.…”
Section: Introductionmentioning
confidence: 99%